WHAT-IF ANALYSIS: DECISION-MAKING MODEL OF CLOSED LOOP SUPPLY CHAIN UNDER UNCERTAINTY CONDITIONS - Mirdan, ALnujamimi Aws Saeed; daban, Maytham Mosa jenker (International Journal of Supply Chain Management, 2019)
Decision making is one of the key tasks in managerial outcomes whereby the effect of any decision matters a lot on the strategic dimensions of the organization. In recent years, due to increased environmental concerns, government regulations and natural resource constraints, and the impact of green laws, the supply chain has been attracting increasing attention. Given that the supplier plays an important role in the supply chain, if it is faced with the risk and disruption of the harmful and important impacts on the supply chain, it is necessary to study and study these conditions. Hence, in this paper, the problem of designing a closed loop supply chain network in terms of supply risk is discussed. In any decision, there are multiple perspectives or variables while are closely associated and these variables decide the overall impact on the scenario. For managerial decision making, there are assorted approaches which are used widely including sensitivity analysis, scenario analysis and many others. This research manuscript is focusing on the aspects of what-if analysis and associated decision making models under uncertainty. The manuscript covers the hidden patterns and perspectives which are mandatory to be associated and included in the process of decision making.